1502 Sick leave benefits by endocrine diseases: a retrospective epidemiological study. (24th April 2018) - Priester, LFT; Vitor, DVS; de Brito, RV; Vitor, DVS; Ferreira, LR
Abstract : Introduction: Endocrine Diseases (ED) have a high prevalence around the world. In 2014, the World Health Organisation estimated that many adults will be affected by thoses diseases, worldwide. ED are classified as many different chronic diseases with distinct aetiologies, and they are some of the main causes of disability, which can negatively influence productivity in active workers. In Brazil, those disabled workers with ED diseases can apply for Sick Leave Benefits granted by the Brazilian National Institute of Social Security (BNISS). This Institute is responsible for granting benefits and salaries for work disability. Methods: This was a retrospective cross-sectional study which evaluated 538 workers receiving temporary sick leave benefits from the BNISS caused by ED. The workers were evaluated from June 2014 until July 2016 and submitted to a structured analysis for data collection including: gender, age, affiliation to the BNISS and International Classification of Diseases (ICD-10) of each worker's ED. Results: The workers were 63, 5% female with mean age of 42 years-old, and the most prevalent individuals age ranged from 30 to 49 years old (44%). The most prevalent diseases were associated with obesity (33%) with ICD-10 E65 and E66, followed by Diabetes (23, 5%) with ICD-10 E10, E11 and E14, and thyroid associated diseases (7, 8%) with codes E01, E03, E04, E05, E06, E07. The employed affiliation to BNISS was found in 66, 5% of females, and 50% of males. Other endocrine diseases were found, as amiloidosis (0, 2%) ICD-10 E85, and other endocrine disturbs (4%) ICD-10 E88. Discussion: The results showed that obesity and diabetes are important risks factors for functional endocrine injuries, enhancing the harmful effects of overweight and hiperglicemic diet to health and quality of life of workers. These data can help new strategies to enhance obesity and diabetes prevention and health promotion programs for workers.